A study on customer expectations towards service quality of homestay in Kota Kinabalu, Sabah / Mohammed Irfan Esmadol - Esmadol, Mohammed Irfan (2014)
This study examined "CUSTOMER EXPECTATIONS OF SERVICE QUALITY TOWARDS HOMESTAY IN KOTA KINABALU, SABAH". The tourism sector has been an important contribution to the national economy. Within the tourism industry, Sabah tourism product such as the homestays programmer was seen as having great potential. Homestays at Sabah offers the opportunity for tourists to stay with their local community or host and most important thing being able to experience the local lifestyle and local culture of the community. Sabah was the second largest state in Malaysia. It lies on the island of Borneo bordering with the northern state of Sarawak, the Sultanate of Brunei and the Indonesian provinces of Kalimantan. It was home to 27 ethnic groups, each with its own distanced language, culture and lifestyle. Sabah also known as the "Land Below The Wind" had all the elements required to become Malaysia's next desirable destination, from natural beauty, history, heritage, festivals to modem city living and luxury. Indeed, it had become a potpourri of experiences appreciated by travelers from all over the world. In Sabah, there were many 'kampung' or villages that were successfully engaged in homestay programmers. This research needs for particular in Sabah homestays because there were limited research on Sabah's homestays among the operators and tourist. The main purpose of this research was to know the critical success factors for homestays in Sabah such as service quality, infrastructure, food tourism, product and promotion. Additionally, the researcher wants to develop profile of homestays in Sarawak and to determine the tourist perception towards homestay business in Sabah. Lastly, it also looks at the potential and the roles of homestays in the alternative tourism contact and in the Sabah tourism scenario.